2021
DOI: 10.3390/ijms23010087
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spatially Heterogeneous Trop-2 Expression on Prognosis in Oral Squamous Cell Carcinoma

Abstract: Oral cancer often presents with aggressive behavior and a high risk of recurrence and metastasis. For oral squamous cell carcinoma (OSCC), which is the most frequent histological subtype, therapy strategies include surgery, radiation therapy, chemotherapy, immune checkpoint inhibitors, and EGFR inhibitors. Recently, a Trop-2 antibody-drug conjugate (ADC) has been approved in the United States of America for the treatment of advanced triple-negative breast cancer. However, this ADC has also been tested in other… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…TROP2 may serve as an independent prognostic biomarker in patients with glioblastoma and oral squamous cell carcinoma. 48 , 49 Furthermore, previous studies have shown that the upregulation of TROP2 plays a critical role in human cancer growth and that tumor development is quantitatively driven by TROP2 expression levels. 50 , 51 Moreover, TROP2 high expression is a suitable marker for stratifying patients with a high risk of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TROP2 may serve as an independent prognostic biomarker in patients with glioblastoma and oral squamous cell carcinoma. 48 , 49 Furthermore, previous studies have shown that the upregulation of TROP2 plays a critical role in human cancer growth and that tumor development is quantitatively driven by TROP2 expression levels. 50 , 51 Moreover, TROP2 high expression is a suitable marker for stratifying patients with a high risk of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we have validated that ICAM1 antigens overexpressed on the surface of human TSCC cells can facilitate rapid and e cient cellular internalization of its monoclonal antibodies, which is a critical consideration factor for ICAM1-ADC development. Besides ICAM1, other cell membrane proteins such as nectin-4 67 , folate receptor 68, 69 , TROP2 70 , and epidermal growth factor receptor (EGFR) 71,72 have also been reported as promising molecular targets for oral squamous cell carcinoma, all of which have been utilized for clinically-approved ADCs (Enfortumab vedotin, Mirvetuximab Soravtansine, and Sacituzumab govitecan) or ADCs in clinical trials (ABT414) 73 . Thus, we compared the levels of nectin-4, folate receptor and TROP2 overexpression in comparison with ICAM1, and found they are approximately 8.01%-98.2% lower.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the PPARγ antibody (1:300 dilution, ab59256, Abcam) was also processed following the same conditions and steps. The stained slides were scanned and quantified using the HALO Highplex FL (Indica Labs; Albuquerque, NM) analysis module of Halo software ( Erber et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%